INTERNET OF MEDICAL THINGS (IoMT)-BASED HEART RATE AND BODY TEMPERATURE MONITORING SYSTEM - Laila, Ida; Arifin, A; Armynah, Bidayatul (Indonesian Physical Review, 2022)
Research has been carried out on a heart rate and body temperature monitoring system based on the Internet of Medical Things (IoMT). This study aims to create a system for monitoring heart rate and body temperature remotely in real-time with measurement results displayed on a web server. This research includes several methods such as developing research concepts based on literature studies, system design consisting of hardware and software design, sensor calibration, web server creation, system testing, and direct data retrieval. The hardware manufacturing stage uses several components such as a pulse heart sensor to detect heart rate, DS18B20 sensor to detect body temperature, Arduino Uno microcontroller, Xbee end device, Xbee coordinator, and raspberry pi as a server computer. Then for the use of software on this system, it consists of Arduino Integrated Development Environment (IDE) to run Arduino Uno hardware, XCTU to provide configuration on Xbee, Python to run Raspberry Pi and Django as a framework for building web servers and MySQL as data storage center measurement results. Heart rate monitoring is done by placing a sensor on one of the fingers, and body temperature is done by placing the sensor in the axilla. The output from the sensor in the form of analog data is converted by the Arduino Uno microcontroller into digital data and then sent to the Raspberry Pi module via Xbee. The raspberry pi has processed data is then stored in the database and then displayed on the webserver. The sensor calibration results show that the pulse heart sensor's error rate is 0.41%, and the DS18B20 temperature sensor is 1.09%. After calibration of the sensor, data was collected on the three respondents' heart rate and body temperature. The measurement results show that the system can store each respondent's heart rate and body temperature data in the database and display the measurement results on the webserver in real-time. Based on these results indicate that the system that has been made can work well.